The history of marine fish systematics in South Africa - Gon, O (Ofer), 1949- (Rhodes University, Faculty of Humanities, Department of History, 2003)
South African marine fish collections and systematic research are relatively young, essentially a product of the 20th century. Their history in South Africa comprises three distinct periods: the emergence of fish collections (before 1895), the beginning of research (1895-1945) and modern research (1945-1999). From the outset of their arrival in South Africa in the mid-17th century, the European settlers of the Cape Colony supplemented their diet with fishes. Therefore it is not surprising that when natural history museums appeared in the 19th century fishes were among the first specimens they procured or received from the public. In these early days, fishes were acquired for display purposes and were curated together with other natural history specimens. There were no fish collections as such and, in many ways, the early history of South African fish collections closely followed the history of the institutions in which they were housed. Major political events in South Africa between 1850-1910 had little effect on the slow growth offish collections as the low influx of specimens from the public did not change. None of the museums did any active fish collecting and no fish research as such took place during these years. The second period in the growth of fish collections in South Africa was characterised by a general shift to collecting for research rather than display. It was also a period during which the need for aquatic research was recognized by and began to attract funding from the South African government, starting with the establishment of the Marine Biological Survey in Cape Town. However, with the exception of the Albany Museum's self-trained J.L.B. Smith, no trained marine fish systematists were working in museums either as curators or as researchers. In the first half of the 20"' century South Africa experienced the fast growth of the fishing industry, the development of academic and applied research in marine biology, and the thriving of sport fishing. These developments created a demand for well-trained professional ichthyologists. J.L.B. Smith was the first to fill this professional gap. The growth rate offish collections increased significantly through the interaction between museum scientists, such as Smith in Grahamstown and K.H. Barnard in Cape Town, with the fishing industry, government biologists and fisheries officers, and anglers. Barnard's review of the South African marine fish fauna was published in mid-I920s. The discovery of the first living coelacanth placed South African ichthyology and Smith on the international stage. The identification of this fish, made by a relatively inexperienced Smith, changed the way ichthyology has been viewed in South Africa. At the beginning of the third period, largely due to the establishment of the Council for Scientific and Industrial Research in 1945, science in South Africa underwent a process of reorganisation. As funding became more available museums were able to enlarge their research staff. Natural history museums hired qualified experts to conduct research and manage collections of specific groups of organisms. For the first time, trained ichthyologists started working in museums and initiated research projects that were the main contributors to the growth of fish collections around the country. Furthermore it was a period of consolidation offish collections resulting in two large marine fish collections, one at the South African Museum, Cape Town, and another at the J .L.B. Smith Institute of Ichthyology, Grahamstown. This period also witnessed the establishment of the latter as a research institute dedicated to the study of fishes and its rise to international prominence. The last 55 years at J.L.B. Smith Institute of Ichthyology can be divided into two distinct periods, 1945-1967 and 1968-1999, each consisting of similar elements of research work and objectives. These included the research and production of major reviews of the fish faunas of South Africa, the western Indian Ocean and the Southern Ocean, as well as research on the coelacanth. While in the former period the work was done by one scientist, J.L.B. Smith, the latter period has been characterised by collaborative projects including scientists from South Africa and abroad. As this history shows, the establishment of a viable, long-lasting collection is a lengthy process. For about 60 years the durability of fish collections depended on the enthusiasm and persistence of individual curators and scientists who were not ichthyologists. More often than not, enthusiasm disappeared when such individuals left their museums. This dependence existed until Rhodes University College established the Department of Ichthyology (1947) and the South African Museum created a post specifically for the curation of the fish collection (1957) and thus ensured continuity. The continuity of biosystematic research in South Africa has been a minor concern for the nation's systematists for decades. The threats to marine fish systematics have been of a financial, political and professional nature. The latter has been the most serious one because of the dearth of South Africans trained in marine fish systematics. After J.L.B. Smith's death in 1968 M.M. Smith had to work hard to convince the Council for Scientific and Industrial Research and Rhodes University that she could step into her late husband's shoes. Realizing that there was nobody to take over from her she initiated the first and only postgraduate programme in ichthyology in South Africa. The teaching started in the academic year of 1970171 at the J.L.B. Smith Institute of Ichthyology, but to date only one student has completed a thesis in marine fish systematics. Due to the government's transformation policy all the practising marine fish systematists in South Africa will be retiring in the course of the present decade. Consequently, if no aspiring, motivated students appear on the scene in the next couple of years marine fish systematics in this country will be in a deep crisis by the year 2010, possibly even earlier.
Keywords: J.L.B. Smith Institute of Ichthyology; Fishes -- Research -- South Africa -- History; Fishes -- Catalogs and collections -- South Africa -- History; Museums -- South Africa